Sex differences of inflammation in target organs, induced intraperitoneal injection of lipopolysaccharide, depend on its dose - Kosyreva AM; Makarova OV; Kakturskiy LV; Mikhailova LP; Boltovskaya MN; Rogov KA (Dove Medical Press, 2018)
Anna M Kosyreva,1 Olga V Makarova,1 Lev V Kakturskiy,2 Liliya P Mikhailova,1 Marina N Boltovskaya,3 Konstantin A Rogov2 1Department of Immunomorphology of Inflammation, Federal State Budgetary Institution “Science Research Institute of Human Morphology”, Moscow, Russia; 2Department of Pathology, Federal State Budgetary Institution “Science Research Institute of Human Morphology”, Moscow, Russia; 3Department of Reproductive Pathology, Federal State Budgetary Institution “Science Research Institute of Human Morphology”, Moscow, Russia Purpose: The aim of our research was to study sex differences and the severity of inflammatory changes in target organs and the peculiarities of immunological disorders when low and high doses of lipopolysaccharide (LPS) were administered to rats. Methods: Male and female 2- to 3-month-old Wistar rats (200–250 g) were injected intraperitoneally with Escherichia coli LPS in one of two doses: 1.5 or 15 mg/kg. In a day after the LPS injection, we studied endotoxin, corticosterone, sex steroids, alanine aminotransferase (ALT), and aspartate aminotransferase (AST) activity levels in the serum; morphological disorders in the lung, liver, thymus, and spleen; ex vivo production of IL-2, IL-4, tumor necrosis factor (TNF), and interferon γ (IFNγ) by splenic cells activated by ConA; and relative amount of T- and B-lymphocytes in the peripheral blood. Results: After the injection of low-dose LPS, the serum endotoxin level increased only in males and was combined with a more pronounced inflammatory response in the lungs and thymus and an increase in ALT and AST activity levels without any changes in corticosterone level. After the injection of high-dose LPS, the inflammatory and pathological changes in the target organs manifested as severe endotoxemia and sex differences of pathological changes in the lungs and liver were not revealed. The level of production of IL-2, IL-4, IFNγ, and TNF by splenic cells and the number of T-lymphocytes, including cytotoxic cells, in the peripheral blood, decreased in males, which is an evidence of a pronounced suppression of the immune response. Conclusion: We have shown that the morphofunctional changes in the organs of the immune system in females and males, as well as the intensity of the sex differences of inflammation, depend on the severity of systemic inflammatory response, induced by different doses of LPS. Keywords: endotoxinemia, SIRS, thymus, spleen, male rats, female rats